Ginseng oral disintegrating adhesive granules and a method for preparing the same
Patent Information
- Application Number
- CN202611243674.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
这些颗粒崩解后迅速随唾液吞咽,无法实现颊黏膜的定向、持续给药,因而难以充分利用口腔黏膜给药的独特优势
本发明通过配方优化,解决了口腔给药中“快速崩解”与“长效黏附”的功能矛盾。本发明提供的人参口腔崩解黏附颗粒能在口腔内30秒内快速崩解,释放的物料能立即主动黏附于颊黏膜,并维持1~3h的有效滞留,真正实现了颊黏膜的持续、高效给药,大幅提高人参活性成分的生物利用度。
Smart Images

Figure CN122911906A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of pharmaceutical preparation technology, and in particular to a ginseng oral disintegration and adhesion granule and its preparation method. Background Technology
[0002] Oral mucosal drug delivery has become an important research direction for novel drug delivery systems due to its advantages such as avoiding the first-pass effect of the liver, improving drug bioavailability, rapid onset of action, and good patient compliance. Among them, the buccal mucosa region, with its rich blood supply, relatively large area, and resistance to saliva erosion, is an ideal site for achieving local or systemic drug delivery.
[0003] Currently, reported buccal mucosal drug delivery formulations mainly include patches, films, gels, and lozenges. However, these formulations still have many limitations in practical applications. For example, patches and films may cause a noticeable foreign body sensation in the mouth, affecting patient comfort and compliance (especially for children and those with swallowing difficulties); gels have a short retention time, and the drug is easily diluted by saliva or swallowed; traditional lozenges usually rely on passive diffusion, with limited contact area and time with the mucosa, and the drug absorption efficiency needs to be improved.
[0004] Ginseng, a traditional and precious Chinese herbal medicine, possesses a variety of pharmacological activities. However, its conventional administration methods (such as oral decoctions, pills, or capsules) have problems such as slow onset of action, and some active ingredients being easily destroyed by the gastrointestinal environment or lost due to the first-pass effect. Currently, there is a lack of a specialized dosage form on the market that can efficiently deliver the active ingredients of ginseng to the buccal mucosa vascular system, thereby achieving rapid absorption.
[0005] While there are studies on orally disintegrating particles, most focus only on improving taste through rapid dispersion on the tongue, and their design is not intended to achieve active and sustained adhesion to mucous membranes. These particles are quickly swallowed with saliva after disintegration, making it impossible to achieve targeted and continuous drug delivery to the buccal mucosa, thus failing to fully utilize the unique advantages of oral mucosal drug delivery.
[0006] Therefore, developing a new formulation that is easy to take and has high compliance, like orally disintegrating granules, and that can actively adhere to the buccal mucosa after disintegration, thus prolonging the drug's residence time at the absorption site, is of great clinical significance and application value for drugs such as ginseng. Summary of the Invention
[0007] In view of this, the purpose of this invention is to provide ginseng oral disintegrating and adhesive granules and a method for preparing the same. The ginseng oral disintegrating and adhesive granules provided by this invention can synergistically achieve rapid disintegration and long-lasting adhesion for continuous drug delivery, and have the advantages of rapid onset of action, high bioavailability, and convenient use.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides ginseng oral disintegrating and adhering particles, which, on a dry weight basis, comprise the following components: 22% ginseng active extract, 5.5% hydroxypropyl methylcellulose, 21.5% crospovidone, 7% menthol, 4.6% microcrystalline cellulose, and the balance mannitol; the viscosity of the hydroxypropyl methylcellulose is 4000 mPa·s; and the moisture content of the ginseng oral disintegrating and adhering particles is <8%.
[0009] This invention provides a method for preparing the ginseng oral disintegrating and adhesive particles described above, comprising the following steps: mixing ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol to obtain a dry powder mixture; The dry powder mixture is mixed with an ethanol-water solution to obtain a soft material; The soft material is extruded into strips and then rolled into rounds to obtain wet granules; The wet granules are dried until the moisture content is less than 8% to obtain the ginseng oral disintegration and adhesion granules.
[0010] Preferably, the ethanol aqueous solution has a mass fraction of 50-60%.
[0011] Preferably, the rounding time is 15 minutes.
[0012] Preferably, the rolling frequency is 30~50Hz.
[0013] Preferably, the drying is performed by forced air drying; the drying temperature is 50°C.
[0014] Preferably, the drying time is 2 hours.
[0015] Preferably, the extrusion is carried out in an extruder; the extrusion frequency is 40~60Hz.
[0016] Preferably, the mixing is an equal-incremental mixing.
[0017] Preferably, before mixing, the ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol are each passed through a 100-mesh sieve.
[0018] Compared with the prior art, the present invention has the following significant advantages: This invention resolves the functional contradiction between "rapid disintegration" and "long-lasting adhesion" in oral drug delivery through formulation optimization. The ginseng oral disintegrating and adhering granules provided by this invention can rapidly disintegrate within 30 seconds in the oral cavity, and the released material can immediately and actively adhere to the buccal mucosa, maintaining effective retention for 1-3 hours. This truly achieves continuous and efficient drug delivery to the buccal mucosa, significantly improving the bioavailability of ginseng's active ingredients.
[0019] Furthermore, this invention also exhibits a significant permeation-enhancing effect: Menthol is introduced as a permeation enhancer. In vitro mucosal permeation experiments using the Franz diffusion cell demonstrate that 7% menthol significantly improves the ability of ginsenoside Rg1, an active ingredient in ginseng, to permeate the mucosa and reduces drug retention in the mucosa. This indicates that it effectively promotes drug penetration through the mucosal barrier to the receptor side, thereby further improving oral mucosal absorption efficiency. Compared to traditional oral administration methods, this invention reduces gastrointestinal degradation and the first-pass effect, improving the utilization efficiency and onset speed of ginseng's active ingredients.
[0020] This invention provides a method for preparing the ginseng oral disintegration and adhesion particles described above. The preparation process of this invention is stable and scalable, yields high-quality adhesion particles, and exhibits good process reproducibility, laying a solid foundation for industrial production. Attached Figure Description
[0021] Figure 1 Photograph of ginseng oral disintegration and adhesion particles prepared in Example 1. Detailed Implementation
[0022] This invention provides ginseng oral disintegrating and adhering particles, which, on a dry weight basis, comprise the following components: 22% ginseng active extract, 5.5% hydroxypropyl methylcellulose, 21.5% crospovidone, 7% menthol, 4.6% microcrystalline cellulose, and the balance mannitol; the viscosity of the hydroxypropyl methylcellulose is 4000 mPa·s; and the moisture content of the ginseng oral disintegrating and adhering particles is <8%.
[0023] In this invention, all components are commercially available products well known in the art.
[0024] This invention does not impose specific limitations on the content of ginsenoside Rg1 in ginseng active extracts, which can be controlled according to actual needs. If required, quality control can be performed using high-performance liquid chromatography (HPLC) that has been validated for specificity, linearity, precision, accuracy, and robustness. In this invention, the ginseng can be various processed products, such as sun-dried ginseng, red ginseng, and black ginseng.
[0025] In this invention, hydroxypropyl methylcellulose (HPMC) is used as a bioadhesive material. This invention utilizes hydroxypropyl methylcellulose (HPMC 4000) with a viscosity of 4000 mPa·s, which possesses excellent adhesive properties, enabling long-term adhesion of ginseng oral disintegration adhesive particles to the buccal mucosa, while maintaining a short disintegration time.
[0026] In this invention, the cross-linked polyvinylpyrrolidone (PVPP) acts as a superdisintegrant, significantly reducing the disintegration time of ginseng oral disintegration and adhesion particles; the menthol acts as a permeation enhancer, effectively promoting the penetration of ginseng extract active ingredients through the mucosal barrier into the receptor side, thereby further improving the oral mucosal absorption efficiency; the microcrystalline cellulose and mannitol act as fillers, maintaining particle morphology while exhibiting optimal disintegration and adhesion times.
[0027] This invention resolves the functional contradiction between "rapid disintegration" and "long-lasting adhesion" in oral drug delivery through formulation optimization. The ginseng oral disintegrating and adhering granules provided by this invention can rapidly disintegrate within 30 seconds in the oral cavity, and the released material can immediately and actively adhere to the buccal mucosa, maintaining effective retention for 1-3 hours. This truly achieves continuous and efficient drug delivery to the buccal mucosa, significantly improving the bioavailability of ginseng's active ingredients.
[0028] In this invention, the particle size of the ginseng oral disintegration and adhesion particles is preferably between 18 mesh and 24 mesh (i.e., the material under 18 mesh sieve and the material over 24 mesh sieve).
[0029] This invention provides a method for preparing the ginseng oral disintegrating and adhesive particles described above, comprising the following steps: mixing ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol to obtain a dry powder mixture; The dry powder mixture is mixed with an ethanol-water solution to obtain a soft material; The soft material is extruded into strips and then rolled into rounds to obtain wet granules; The wet granules are dried until the moisture content is less than 8% to obtain the ginseng oral disintegration and adhesion granules.
[0030] This invention mixes ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol to obtain a dry powder mixture.
[0031] In this invention, before mixing, it is preferable to pass each component through a 100-mesh sieve and collect the undersize material. In this invention, the mixing is preferably performed by increasing the mixing volume in equal increments.
[0032] After obtaining the dry powder mixture, the present invention mixes the dry powder mixture with an ethanol aqueous solution to obtain a soft material.
[0033] In this invention, the mass fraction of the ethanol aqueous solution is preferably 50-60%, and in specific embodiments it can be 50%, 55%, or 60%, more preferably 50%. This invention uses the above-mentioned mass fraction of ethanol aqueous solution as a binder or wetting agent to produce a soft material with moderate hardness and agglomeration, while also obtaining uniformly sized adhesive particles. When the mass fraction of the alcohol solution is >60%, it leads to difficulties in granulation and uneven particle size. This invention does not impose a special limitation on the amount of the ethanol aqueous solution; it is sufficient to produce a soft material that "clumps when grasped but crumbles upon contact."
[0034] After obtaining the soft material, the present invention extrudes the soft material into strips and rolls them into rounds to obtain wet granules.
[0035] In this invention, the extrusion is preferably carried out in an extruder, and the extrusion frequency is preferably 40-60 Hz, which can be 40, 50, or 60 Hz in specific embodiments. From a cost perspective, the extrusion frequency is preferably 60 Hz.
[0036] In this invention, the rounding is preferably performed in a rounding machine; the rounding frequency is preferably 30-50 Hz, and in specific embodiments it can be 30, 40, or 50 Hz. From a cost perspective, the rounding frequency is preferably 50 Hz. In this invention, the rounding time is preferably 15 minutes. Controlling the rounding time in this invention ensures a high yield (>93%) of ginseng oral disintegration and adhesion particles.
[0037] After obtaining the wet granules, the present invention dries the wet granules to a moisture content of less than 8% to obtain the ginseng oral disintegration and adhesion granules.
[0038] In this invention, the drying is preferably performed by forced air drying; the drying temperature is preferably 50°C; the drying time is not specifically limited, and drying is sufficient until the moisture content is below 8%. From a cost perspective, the drying time is preferably 2 hours.
[0039] After the drying process is completed, the present invention preferably further includes sieving the dried particles to obtain ginseng oral disintegration and adhesion particles of the target size.
[0040] The parameters controlled by this invention, especially the spheroidizing time, ensure excellent particle yield and good process reproducibility, laying a solid foundation for industrial production.
[0041] The following detailed description of the ginseng oral disintegration and adhesion particles and their preparation method provided by the present invention, with reference to the embodiments, should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1 The specific prescription for the red ginseng oral disintegration and adhesion granules provided in this embodiment is as follows: Red ginseng active extract: 22g, hydroxypropyl methylcellulose 4000: 5.5g, crospovidone: 21.5g, menthol: 7g, mannitol: 39.4g, microcrystalline cellulose: 4.6g.
[0043] The method for preparing the red ginseng oral disintegration and adhesion particles is as follows: Mixing: Pass the red ginseng active extract, hydroxypropyl methylcellulose, crospovidone, mannitol, and microcrystalline cellulose through a 100-mesh sieve. Mix them evenly using an equal-incremental method to obtain a dry powder mixture.
[0044] To make a soft material: Slowly add an appropriate amount of 50% ethanol aqueous solution to the dry powder mixture and stir continuously to make a soft material that "can be formed into a ball when squeezed and crumbles when touched".
[0045] Extrusion: The soft material is fed into the extruder, the extrusion frequency is set to 60Hz, and it is extruded into strips with a diameter of about 1mm.
[0046] Rounding: Transfer the extrudate to a rounding machine, set the rounding frequency to 50Hz, and the rounding time to 15min to obtain wet granules.
[0047] Drying: Place the wet granules in a forced-air drying oven, with an inlet air temperature of 50℃, and dry for 2 hours.
[0048] Granulation: After drying, the granules are passed through 18-mesh and 24-mesh sieves, and the granules between the sieves are collected to obtain the oral disintegration and adhesion granules of red ginseng (actual product photo as shown). Figure 1 (As shown).
[0049] Test Example 1: Optimization of Red Ginseng Orally Disintegrating Adhesive Particle Formula 1. In this test example, the extrusion-spheronization method was used to prepare the particles. The specific process is as follows: Red ginseng active extract (RGE) was added to excipients, passed through a 100-mesh sieve, ground and mixed evenly, and a wetting agent was added to make a soft material. The material was then extruded into similar strip-shaped columns through an extruder (1.0 mm aperture). The speed of the rounding machine was adjusted to 50 Hz and the rounding time to 15 min. The strip-shaped material was completely rounded by friction to obtain pellets. The pellets were dried at 50℃ for 1 h and then granulated by passing through a 20-mesh sieve to obtain granules.
[0050] 2. Evaluation indicators and measurement methods: Based on the characteristics of disintegrating and adhering particles, in vitro adhesion time, disintegration time, and particle morphology were determined as the evaluation indicators.
[0051] (1) Determination of in vitro adhesion time: In order to simulate the time that oral particles can stay in the oral cavity after being affected by mechanical factors such as saliva flow and rinsing, the following device was specially made: The upper part is a linear reciprocating mechanical device, and a glass slide is fixed on the telescopic lever. The glass slide is coated with 5% (w / w) mucin solution to simulate the oral mucosa surface. Red ginseng oral particles are attached to its surface, and a 2 g weight is placed on the particle surface for 30 s. The lower part uses artificial saliva as the test medium. The glass slide moves up and down. The upper edge of the particle is immersed in the artificial saliva, and the lower edge leaves the artificial saliva as 1 time. The mechanical device is set to 60 times / min. The time when the particle completely detaches from the glass slide is recorded to simulate the residence time of oral particles in the oral cavity.
[0052] (2) Disintegration time determination: Weigh 6 portions of 0.500 g qualified particles and place them in the basket of the disintegrator. Observe that the particles have no hard core, which is the disintegration time. Repeat the experiment 3 times and calculate the average value.
[0053] 3. Single-factor analysis of granule formulation prescription types Granules were prepared according to the process described in Part 1. Single-factor experiments were conducted to determine the drug loading of the granules, the types of fillers in the formulation (microcrystalline cellulose (MCC), lactose, mannitol), the types of disintegrants (sodium carboxymethyl starch (CMS-Na), low-substituted hydroxypropyl cellulose (L-HPC), cross-linked polyvinylpyrrolidone (PPVP)), the types of adhesive polymers (hydroxypropyl methylcellulose (HPMC400, HPMC4000), carbomer, chitosan), and the types of binders (wetting agents) (50% ethanol, 55% ethanol, 60% ethanol, 65% ethanol, 70% ethanol).
[0054] (1) Investigation of filler types Weigh 4 parts of RGE and mix them evenly with MCC, lactose, mannitol, and MCC+mannitol respectively in proportion. The ratio of REG to filler is 1:2. When the filler is MCC+mannitol, MCC accounts for 5% of the total formula, and the remainder is mannitol (that is, the filler accounts for 33.3% of the total formula, of which MCC accounts for 5%). Use 50% ethanol as a wetting agent to prepare soft material, extrude and roll it into rounds, dry and sieve it, and then use a comprehensive scoring method to evaluate the particles.
[0055] The results showed that when MCC and mannitol were used together as fillers, the particle morphology was optimal, and the disintegration and adhesion times were also superior. Therefore, MCC+mannitol was selected as the filler.
[0056] Table 1. Results of the investigation of fillers
[0057] (2) Drug loading investigation RGE is a hygroscopic drug, and its dosage in the formulation determines the quality of the granules. This application selected MCC and mannitol as excipients and investigated their dosages. The mass ratio of RGE to filler was 2:1, 3:2, 1:1, 2:3, and 1:2 (with MCC fixed at 5% of the total formulation). The wetting agent was a 50% aqueous ethanol solution. The in vitro adhesion time and disintegration time of the granules were measured, and the granule morphology was observed to determine the optimal drug loading.
[0058] The results showed that the particle morphology was optimal when the mass ratio of RGE to mannitol was 1:2, and the disintegration time was <30s. The in vitro adhesion time also met the requirements. Therefore, the optimal drug loading was selected when the mass ratio of RGE to filler was 1:2.
[0059] Table 2 Results of Drug Loading Investigation
[0060] (3) Investigation of disintegrant types Weigh 4 portions of RGE. Based on the preliminary experimental results, add MCC (5%), mannitol (43.7%), and HPMC4000 (5%) to each portion according to the corresponding proportion of the total formula. Then mix them with disintegrants 22% CMS-Na, 22% SSG, 22% PPVP, and 11% PVPP + 11% CMS-Na evenly. Use 50% ethanol as a wetting agent to make soft material. Extrude and roll into rounds. After drying and sieving, evaluate the particles according to the disintegration time.
[0061] The results showed that PVPP had the shortest disintegration time, so PVPP was selected as the best disintegrating agent.
[0062] Table 3 Results of the investigation on the types of disintegrants
[0063] (4) Investigation of the types of adhesive polymers Weigh 4 portions of RGE. Based on the results of preliminary experiments and the investigation of disintegrant types, add the corresponding proportions of MCC (5%), mannitol (43.7%), and PVPP (22%) to each portion. Then add 5% carbomer, 5% HPMC400, 5% HPMC4000, 5% chitosan, and an appropriate amount of 50% ethanol to make soft material. Extrude and roll into rounds, dry and sieve. Evaluate the particles based on the in vitro adhesion time and disintegration time.
[0064] The results show that HPMC4000 has the longest adhesion time and the shortest disintegration time when used as an adhesive material, therefore HPMC4000 is selected as the best adhesive material.
[0065] Table 4 Results of the investigation on adhesive polymer types
[0066] (5) Investigation of adhesive (wetting) agent types Weigh 5 parts of RGE. Based on the results of drug loading, filler, disintegrant, and adhesive polymer analysis, add appropriate proportions of MCC, lactose, PVPP, and HPMC 4000 to each part. Then add appropriate amounts of 50% ethanol, 55% ethanol, 60% ethanol, 65% ethanol, and 70% ethanol to prepare a soft material. Extrude and roll the material into rounds, dry and sieve it, and observe the particle morphology to determine the type of adhesive.
[0067] The results showed that when 50-60% ethanol was used as a wetting agent, there was no clumping of soft material, the material was of moderate softness and hardness, and the particle size was uniform. To save costs, 50% ethanol was selected as the best wetting agent.
[0068] Table 5 Results of the investigation on wetting agent types
[0069] 4. Optimization of particle formulation composition using Box-Behnken response surface methodology The experimental design and results are shown in Table 6. Experimental data were analyzed using Design Expert 13. Multiple nonlinear regression was performed on the three selected factors, with particle disintegration time and in vitro adhesion time as evaluation indicators (Y1) and (Y2). Contour plots and three-dimensional response surface plots of the two indicators and the three factors were then plotted using the software.
[0070] Table 6. Experimental Results of Bok-Behnken Response Surface Design
[0071] The data in the table were statistically processed using Design Expert 13 software. The multivariate nonlinear fitting equations and correlation coefficients of disintegration time on each factor are as follows: Y=17.40-5.25*A-1.75*B+2.75*C+4.75*AB+2.75*AC+2.25*BC+11.43*A 2 +14.43*B 2 +16.43*C 2 ,R 2 =0.9930. Analysis of variance of the model shows that p < 0.01, indicating a significant model; p = 0.0868, indicating a non-significant lack of fit; and the equation has a good fit.
[0072] Table 7. Results of the analysis of variance for the time-disintegration regression model.
[0073] The data in the table were statistically processed using Design Expert 13 software. The multivariate nonlinear fitting equations and correlation coefficients for each factor under different in vitro adhesion times are as follows: Y=128.8-17.12*A+23.00*B-4.62*C-10.00*AB+0.7500*AC-1.50*BC-24.28*A 2 -27.03*B 2 -17.77C 2 R 2 =0.9954. Analysis of variance of the model shows that p < 0.01, indicating a significant model; p = 0.0868, indicating a non-significant lack of fit, and the equation has a good fit.
[0074] Table 8. Results of ANOVA for the regression model of in vitro adhesion time.
[0075] Using the analysis module of Design-Expert 10.0 software, a three-dimensional effect surface plot and contour plot of the interaction of various factors on the total score were plotted. It was found that the dosages of PVPP (A), HPMC (B), and MCC (C) all had a certain degree of influence on particle disintegration time and in vitro adhesion time. After processing the experimental results using Design-Expert 13 software, the optimized formulation was obtained using the minimum disintegration time and the longest in vitro adhesion time as evaluation indicators: HPMC: 5.5%, PVPP: 21.5%, MCC: 4.6%. When HPMC was 5.5%, PVPP was 21.5%, and MCC was 4.6%, both disintegration time and adhesion time were significantly better than other combinations, indicating that this specific ratio produced a synergistic effect, rather than a simple additive effect.
[0076] Test Example 2: Effect of Permeability Enhancers on Drug Absorption Through Mucosal Membranes Preparation of the solution for the supply tank: Weigh 110.0 mg of Rg1 reference standard, dissolve it in 10 mL of pH 6.8 PBS solution, shake for 1 h, sonicate for 1 h, and prepare 10 mL of red ginseng extract supply solution containing the same concentration (11 mg / mL) of Rg1. Store the supply solution at 4℃ for later use. Before use, vortex the supply solution for 5 min.
[0077] Preparation of the penetration enhancer solution: Decanoic acid, menthol, and propylene glycol were dissolved in 95% ethanol to obtain decanoic acid solution (0.5%~2% w / v), menthol solution (3%~7% w / v), and propylene glycol solution (3%~7% w / v), respectively.
[0078] In vitro permeation experiment: The treated porcine esophageal epithelium was clamped in the center of the Franz diffusion chamber (diffusion area 1.76 cm²). 2 (The receiving chamber solution volume is 4.5 mL). Position the pig esophageal epithelium with the outer layer facing the supply chamber and the inner layer facing the receiving chamber. Add 1.0 mL of pH 6.8 PBS solution to the supply chamber. After 5 minutes, check the receiving chamber for leaks caused by damage to the pig esophageal epithelium or improper installation of the diffusion chamber. If no leaks are found, discard the supply chamber solution and wipe it dry. Add 40.0 μL of osmosis enhancer solution to the supply chamber and leave it open for 1 hour to ensure the ethanol solvent evaporates and removes solvent interference. Add 4.5 mL of pH 7.4 PBS solution to the receiving chamber and 0.2 mL of supply solution to the supply chamber. Place the Franz diffusion cell on a transdermal diffusion apparatus, add a magnetic stir bar, and set the rotation speed to 600 rpm / min and the temperature to 37℃±0.5℃. At 0, 0.25, 0.5, 0.75, 1, 1.5, 2.5, 3, and 4 h, respectively, 0.3 mL of receiving solution is drawn from the receiving chamber, and 0.3 mL of fresh isothermal pH 7.4 PBS buffer is added to the receiving chamber. After the detection is complete, all samples are filtered through a 0.22 μm filter membrane. The filtrate is analyzed using the following chromatographic method: Hypersil ODS (4.6×250 mm, 5 µm), mobile phase: water: acetonitrile = 77:23, flow rate: 1 mL / min, temperature: 30℃, injection volume: 20 μL, absorbance: 203 nm. The results are then substituted into the standard curve for calculation. The cumulative amount of drug permeated during the 4-hour permeation process was calculated, and the permeation-enhancing effects of each permeation enhancer were compared. The experimental results are shown in Table 9.
[0079] As shown in Table 9, the 7% menthol group had the highest cumulative drug penetration over 4 hours, indicating that menthol had the best permeation-enhancing effect as a permeation enhancer. Therefore, 7% menthol was selected as the permeation enhancer in the prescription.
[0080] Table 9. Effects of different penetration enhancers on the cumulative in vitro permeation of ginsenoside Rg1.
[0081] In vitro permeation verification experiment: For the in vitro permeation validation experiment, red ginseng extract was used as the model drug, the Franz diffusion cell as the permeation device, and porcine esophageal mucosa as the permeation barrier. The drug concentration at different time points was detected through in vitro mucosal permeation experiments, and the cumulative permeation rate over 4 hours was calculated to compare the permeation-enhancing effects of permeation enhancers. The cumulative permeation rate of the 7% menthol group over 4 hours was 86.35 μg / cm³. 2 Higher than the control group by 3.49 μg / cm 2 This demonstrates that 7% menthol has a permeation-enhancing effect on red ginseng extract.
[0082] Table 10 Effect of 7% Menthol on Cumulative Permeation of Red Ginseng Extract in Vitro
[0083] Drug retention test on mucosal membrane: After the osmotic experiment, the porcine esophageal epithelium was removed from the Franz diffusion cell. Excess tissue in the non-permeable area was trimmed with surgical scissors. The mucosa was repeatedly rinsed with ultrapure water for 30 seconds and dried with filter paper. The mucosa was placed in a 5 mL tube, minced with surgical scissors, and 2 mL of methanol was added. The mixture was sonicated for 1 h, followed by centrifugation at 10,000 rpm for 15 min. 1 mL of the supernatant was collected, filtered through a 0.22 μm filter membrane, and analyzed using liquid chromatography. The results are shown in Table 11.
[0084] Table 11 shows that the average mucosal retention of the drug in the 7% menthol group was 54.03 mg / g, while the average mucosal retention of the drug in the blank group was 83.61 mg / g. This indicates that the mucosa has a storage function, and the greater the retention, the less drug permeates.
[0085] Table 11 Effect of 7% Menthol on Mucosal Retention of Red Ginseng Extract
[0086] Test Example 3: Comparative Experiment on the Synergistic Effect of Oral Disintegration and Adhesion Particles in Red Ginseng To verify the effect of the synergistic combination of bioadhesive material and superdisintegrant on particle performance in this invention, groups without HPMC, without PVPP, ordinary oral disintegrating particles, and the group of this invention were prepared respectively, and the disintegration time and in vitro adhesion time of each group of particles were compared.
[0087] Grouping: (1) HPMC was not added to the formulation of the HPMC-free group, and the other components were the same as in Example 1.
[0088] (2) No PVPP was added to the formulation of the PVPP-free group, and the other components were the same as in Example 1.
[0089] (3) The present invention group prepared red ginseng oral disintegration and adhesion particles according to the prescription of Example 1.
[0090] The disintegration time and in vitro adhesion time of each group of particles were determined according to the method in Part 2 of Test Example 1. Each group was measured in triplicate, and the average value was taken. The test results are shown in Table 12.
[0091] Table 12 shows that HPMC and PVPP have a significant impact on the disintegration and adhesion properties of the particles. Specifically, removing HPMC significantly shortens the in vitro adhesion time, while removing PVPP significantly prolongs the disintegration time. Our invention, through the synergistic combination of HPMC and PVPP, maintains a relatively fast disintegration rate while still achieving a relatively long in vitro adhesion time, thus achieving a synergistic balance between rapid particle disintegration and long-term adhesion performance.
[0092] Table 12 Comparison of disintegration time and in vitro adhesion time of granules with different formulations
[0093] Test Example 4: Optimization of the Preparation Process of Red Ginseng Oral Disintegration Adhesion Particles Orthogonal experiment to optimize process parameters Preliminary experimental analysis revealed that the main factors affecting pellet formability are extrusion frequency (A, Hz), rolling frequency (B, Hz), and rolling time (C, min). Therefore, these three factors were selected for orthogonal experiment design. The optimal process parameters were determined using yield as the indicator. The L9(3)0 ... 4 Orthogonal design experiments were used to optimize the process parameters for preparing red ginseng oral granules by extrusion spheroidization.
[0094] Table 13 Factors and Levels
[0095] The experimental design and results are shown in Table 14, and the analysis of variance is shown in Table 15. The results show that the influence of each factor is C>B>A. Factor A has no significant effect on the results; to reduce costs, level C3 is chosen, and intuitive analysis indicates that level A3 is the best choice. Factor B has no significant effect on the results; to reduce costs, level B3 is chosen, and intuitive analysis indicates that level B3 is the best choice. Factor C has a significant effect on the results; intuitively, level C3 is the best choice. Therefore, the optimal formulation is A3B3C3, which corresponds to an extrusion frequency of 60Hz, a rounding frequency of 50Hz, and a rounding time of 15min.
[0096] Table 14 Experimental Design and Results
[0097] Table 15 Results of Analysis of Variance (ANOVA) R 2 = 0.994)
[0098] A. Extrusion frequency did not show a significant difference (p>0.05), indicating that A. Extrusion frequency does not have a significant relationship with yield. B. Rounding frequency did not show a significant difference (p>0.05), indicating that B. Rounding frequency does not have a significant relationship with yield. C. Rounding time showed a significant difference (p<0.05), indicating that C. Rounding time has a significant relationship with yield.
[0099] Drying temperature and drying time were investigated. To avoid unsuitable drying temperature leading to poor particle properties, or excessive moisture content making the particles difficult to store, the soft material was prepared according to the method of Example 1 and sieved, and the effects of drying at 50°C for 1 h, 1.5 h, 2 h, and 4 h were investigated, using particle properties and moisture content as indicators.
[0100] The results of the screening for drying temperature and time are shown in Table 16. The drying method selected was forced-air drying. According to the moisture content requirements for granules in the 2025 edition of the Chinese Pharmacopoeia, the moisture content should be less than 8%, and the drying time was determined to be 2 hours.
[0101] Table 16 Moisture content (%) of particles at different drying temperatures and times
[0102] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A ginseng oral disintegration and adhesion granule, characterized in that, On a dry weight basis, it comprises the following components: 22% ginseng active extract, 5.5% hydroxypropyl methylcellulose, 21.5% crospovidone, 7% menthol, 4.6% microcrystalline cellulose, and the balance mannitol; the viscosity of the hydroxypropyl methylcellulose is 4000 mPa·s; and the water content of the ginseng oral disintegration and adhesion particles is <8%.
2. The method for preparing the ginseng oral disintegration and adhesion particles according to claim 1, characterized in that, Includes the following steps: Ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol were mixed to obtain a dry powder mixture; The dry powder mixture is mixed with an ethanol-water solution to obtain a soft material; The soft material is extruded into strips and then rolled into rounds to obtain wet granules; The wet granules are dried until the moisture content is less than 8% to obtain the ginseng oral disintegration and adhesion granules.
3. The preparation method according to claim 2, characterized in that, The ethanol aqueous solution has a mass fraction of 50-60%.
4. The preparation method according to claim 2, characterized in that, The rolling time is 15 minutes.
5. The preparation method according to claim 2 or 4, characterized in that, The rolling frequency is 30~50Hz.
6. The preparation method according to claim 2, characterized in that, The drying process is performed by forced-air drying; the drying temperature is 50°C.
7. The preparation method according to claim 6, characterized in that, The drying time is 2 hours.
8. The preparation method according to claim 2, characterized in that, The extrusion is carried out in an extruder; the extrusion frequency is 40~60Hz.
9. The preparation method according to claim 2, characterized in that, The mixing is an equal-incremental mixing.
10. The preparation method according to claim 2 or 9, characterized in that, Before mixing, the ginseng active extract, hydroxypropyl methylcellulose, crospovidone, menthol, microcrystalline cellulose and mannitol are each passed through a 100-mesh sieve.